Simultaneous Electrochemical Measurement using Paper Fluidic Channel on CMOS Chip - Jun Eguchi; Katsuyuki Yamaoka; Shigeyasu Uno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper described the new system of biosensing using CMOS chip. The system was expected to be used in various circumstances because it was suitable for miniaturization compared to the conventional system. To conduct electrochemical measurements, the new system used paper fluidic channel set on the CMOS chip to transport solution to the on-chip electrodes. The materials of paper fluidic channel were only paper and silicone resin, and these were biocompatible. In experiment, we carried out simultaneous detection of glucose and ethanol in liquid sample solutions on the 5mm square CMOS chip and paper fluidic channel. Furthermore, this system can detect various target molecules in addition to glucose and ethanol, and increase number of simultaneous measurement by adding some more process to the paper and CMOS chip.